Delimitation of maritime boundary between Vietnam and China in the Gulf of Tonkin. - Huang, Dongdong. (University of Ottawa (Canada), 1992)
This dissertation begins with a general description of facts, both physical and non-physical, on the dispute in the Gulf of Tonkin. The context in which the dispute arose is given first so that the reader can understand the background of the dispute in terms of both its regional setting (the South China Sea region) and its place in the overall bilateral disputes between Vietnam and China. Next, the physical aspects of the dispute, including coastal configuration, islands, resources, and geomorphological and geological conditions, are described. Then the development of the dispute and the positions of the parties are outlined. The second and third parts of the thesis attempt to answer three questions: (1) What rules and principles of international law are applicable to the delimitation of the territorial seas, exclusive economic zone, and continental shelf in the Gulf of Tonkin? (2) Did the 1887 Sino-French Convention establish the maritime boundary between Vietnam and China in the Gulf of Tonkin? (3) What is the course of the single maritime boundary between Vietnam and China in the Gulf of Tonkin from the eastern point of Tra Co to the closing line of the Gulf? In the examination of the applicable law, the rules on maritime delimitation are classified into legal principles, equitable criteria, relevant circumstances, and practical methods. A boundary line is drawn in the Gulf of Tonkin to illustrate the equitableness of the result reached in the research. The delimitation line was divided into three segments. In the first segment (from the land boundary terminus to the mid-point of oppositeness of coastal relationship), the basic criterion of equal division of the overlapping area requires the adoption of the bisector method based on the general direction of the coasts. Given the roughly equal lengths of the respective coasts of the Parties, the bisector line satisfies the equitable requirements. In the second segment, a median line is drawn from the end-point of the bisector line to the closing line of the Gulf of Tonkin so as to reflect the prevailing oppositeness of the coastal relationship. Finally, the presence and size of the Archipelago des Fai Tsi Long are taken into account in the same way as the Bijago Archipelago was in the Guinea--Guinea-Bissau case, that is, as a certain percentage of the length of the coast of Vietnam. (Abstract shortened by UMI.)
Keywords: Geography.